2007
DOI: 10.1002/macp.200600558
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐oxazoline)s: Alive and Kicking

Abstract: The development of various living/controlled polymerization techniques has allowed the synthesis of a large variety of well‐defined (co)polymers with varied polymer length, composition, and architecture, for example. Screening this large possible parameter space for a polymer with certain properties can be a very demanding process. Therefore, we aim to rapidly synthesize and systematically screen libraries of copolymers to determine structure‐property relationships that might allow the future design of novel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
93
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 61 publications
(58 reference statements)
1
93
0
1
Order By: Relevance
“…Aspects of advanced macromolecular engineering of polyoxazolines, including side-and end-chain functionalization, synthesis and properties of block and random copolymers, etc., have very recently been assorted by Hoogenboom [9,10], Schlaad et al [11], and Makino and Kobayashi [12]. The use of fatty acid based monomers for the preparation of sustainable poly(2-oxazoline)s was also recently highlighted by Hoogenboom [13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aspects of advanced macromolecular engineering of polyoxazolines, including side-and end-chain functionalization, synthesis and properties of block and random copolymers, etc., have very recently been assorted by Hoogenboom [9,10], Schlaad et al [11], and Makino and Kobayashi [12]. The use of fatty acid based monomers for the preparation of sustainable poly(2-oxazoline)s was also recently highlighted by Hoogenboom [13].…”
Section: Introductionmentioning
confidence: 98%
“…Not considered are other emerging applications of poly(2-oxazoline)s, for instance in the fields of biomedicine and life sciences, where POXylation is being successfully introduced as an alternative to PEGylation [14], which has very recently been reviewed elsewhere [15]. Rather than trying to present a comprehensive overview of the literature as was done in other recent articles [9][10][11][12][13], it is aimed to introduce the importance and potential of bioinspired poly(2-oxazoline)s based on selected key references from the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…The cationic ring-opening polymerization (CROP) of 2-oxazolines [1][2][3][4][5][6] proceeds in a living manner under appropriate conditions [7,8]. A cationic species is formed by utilizing a suitable electrophilic initiator, which is prone to undergo attack the nitrogen atom of the oxazoline ring.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense few nonionic polyoxazoline surfactants based on vegetable biomass have been synthesized from glycerol [14] and lipopolymers [15][16][17][18]. Schubert et al have recently reported the synthesis of amphiphilic poly(2-ethyl-2-oxazoline-block-2-"soyalkyl"-2-oxazoline) copolymers from soybean fatty acid [19,20]. The polyoxazoline block was synthesized using a new oxazoline monomer containing a C18 long unsaturated chain issued from soybean oil.…”
Section: Introductionmentioning
confidence: 99%